Exploring Two Methods of Usability Testing: System Usability Scale And Retrospective Think-Aloud - I Wayan Pio Pratama; Eka Sudarsana I Putu Eka Sudarsana; Angling Angling Galih Cahaya Widiyanto (Pusat Penelitian dan Pengabdian Politeknik eLBajo Commodus, 2023)
This research was conducted to measure the usability of a system using two methods, RTA (Retrospective Think Aloud) and SUS (System Usability Scale). An object used in this research was shazam. The subject were 5 people, who are smartphone users in the age range of 10 to 50 years old. Finally, in this research RTA method showed that the shazam application is effective with a completion rate of 94.3% and efficient with a time-based efficiency of 0.108 task/second. While SUS showed that Shazam is still categorized as a class B application.